Heavy Metal Ion Adsorption Properties of Methacrylamidocysteine-Containing Porous Poly(Hydroxyethyl Methacrylate) Chelating Beads - Adil Denizli; Bora Garipcan; Sibel Emir; Süleyman Patir; Ridvan Say (Adsorption Science & Technology)
Details of the adsorption performance of poly(2-hydroxyethylmethacrylate–methacrylamidocysteine) [p(HEMA–MAC)] beads towards the removal of heavy metal ions from aqueous solution were studied. The metal-complexing ligand and/or co-monomer MAC was newly synthesized from methylacrylochloride and cysteine. Spherical beads of average size 150–200 mm were obtained by the radical suspension polymerization of MAC and HEMA conducted in an aqueous dispersion. The p(HEMA–MAC) beads obtained had a specific surface area of 18.9 m 2 /g. p(HEMA–MAC) beads were characterized by swelling studies, FT-IR spectroscopy and elemental analysis. Such beads with a swelling ratio of 72%, and containing 3.9 mmol MAC/g, were used for heavy metal removal studies. The adsorption capacities of the beads for selected metal ions, i.e. Cd II , As III , Cr III , Hg II and Pb II , were investigated in aqueous media containing different amounts of these ions (10–750 mg/l) and at different pH values (3.0–7.0). The adsorption rate was fast in all cases. The maximum adsorption capacities of the p(HEMA–MAC) beads were 1058.2 mg/g for Cd II , 123.4 mg/g for As III , 199.6 mg/g for Cr III , 639.1 mg/g for Pb II and 1018.6 mg/g for Hg II . On a molar basis, the following affinity order was observed: Cd II > Hg II > Cr III > Pb II >As III . The adsorption capacity of the MAC-incorporated beads was affected significantly by the pH value of the aqueous medium. The adsorption of heavy metal ions from artificial wastewater was also studied. In this case, the adsorption capacities were 52.2 mg/g for Cd II , 23.1 mg/g for Cr III , 83.4 mg/g for Hg II , 62.6 mg/g for Pb II and 11.1 mg/g for As III at an initial metal ion concentration of 0.5 mmol/l. The chelating beads could be regenerated easily with a higher effectiveness by 0.1 M HNO 3 . These features make p(HEMA–MAC) beads potential candidates for heavy metal ion removal at high capacity.